PENGGUNAAN MEDIA TRAINER AC SEB AGAI UPA YA MENINGKATKAN KOMPETENSI SISWA PADA MATA DIKLAT TEKNIK PENDINGIN KELAS m LPB Di SMK NEGERI5 SURAKARTA - Sukidi Sukidi (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2010)
This research was aim to: 1) repair to process learning of through utilization trainer Air Conditioning (AC) media. 2) improvement to competence'student in the class student in LPB at the technique of cooler through utilization trainer Air Conditioning (AC) media. The research use the research type action of which base on the class. The research of action class this execute at student class III LPB SMK 5 of state town Surakarta which amount to 33 student. The research of action class this consist of four component that is: a) planning, b) action, c) perception observing, d) reflecting. Fourth component of which in the form of the cycle approach. The research was get to data: 1) observation and 2) test. The especial instrument in research this was researcher by self by means of assist for the which cover: 1) observation/job sheet, and 2) achievement tes. Technique of analysis data in research this use to analyse descriptive quantitative and qualitative. To data improvement of competence'student the items the technique of cooler with tes achievement learn the analysis with technique descriptive quantitative. This research was fmd out that in the learning trainer Air Conditioning (AC) media can be improve to competence's student the interest the technique of cooler at student class m LPB SMK 5 at Surakarta town. Matter this the mark from result indicator of efficacy research of action class and existence of improvement of competence's student (achievement learn) the technique of cooler. The result was done pre-action equal to 6,00, cycle I equal to 7,17, and cycle II equal to 7,44, while to attainment goal finish to learn individual at cycle I equal to 57,58 % (19 student) and cycle II equal to 87,88 %. (29 student) Attainment of achievement learn at cycle I the enough, while cycle II pertained good. Keyword; Trainer Air Conditioning (AC) Media, Competence's student